Capillary Shock Phenomenon of Groundwater at the Beginning of Rainy Season - Panguriseng, Darwis; Nanda, Abd. Rakhim (International Journal on Advanced Science, Engineering and Information Technology, 2018)
This study aims to determine the causes of decreased water level phenomenon that occurred in the early period of the rainy season. This phenomenon became anti-logic because when the rainwater has entered the soil surface layer, instead of groundwater in the saturated layer decreased (decline). This study is experimental field research conducted in Takalar. This research found that the phenomenon of decreased water level in the early period of the rainy season triggered by increasing of capillary pressure due to shrinking pore diameter after water began to infiltrate into the surface soil layer, i.e., the layer of the vadose zone. Increasing of capillary pressure caused the attraction of groundwater in the saturated zone to the vertical direction, so that the groundwater level has decreased significantly. Therefore, this phenomenon was called by the researcher as “capillary shock phenomenon." (2) The lowest groundwater level did not occur in the climax period of the dry season, but it happened in the early period of the rainy season. The phenomenon that took place during the climax of the dry season was the capillary pressure conditions in the lowest layer of the soil because soil pore diameter reached maximum conditions due to the high evaporation process. Groundwater pumping did not solely cause saltwater intrusion into fresh groundwater zone, but it also could be caused by groundwater decrease for each early period of the rainy season.